Applications of resistive droop control to grid connected low-voltage, single phase distributed generators in microgrids - Bontorno, Peter (Kansas State University, 2020)
A common understanding of the future grid structure consists of microgrids connected together (also called grid of microgrids). The microgrid concept includes a collection of loads and distributed generators (e.g. photovoltaic, microturbine, wind, etc.). The intelligent control of microgrids is a widely studied area. Traditionally the grid is controlled by central generators (e.g. nuclear, hydro and coal power stations) which establish the voltage and current setpoints and profiles throughout the grid. As distributed generators are introduced and microgrids are formed the opportunity for decentralized control of grid parameters is realized. While decentralized control can be accomplished by means of communication cables between generators, techniques such as droop control allow distributed generators to locally monitor parameters while collective manage voltage, current and power flow through the microgrid. This paper focuses on decentralized control without the use of communication cables by means of droop control methodologies. Today many low voltage distributed generators, such as rooftop mounted photovoltaic arrays, are implemented using a control method that maximizes power output. This paper investigates the methods of applying droop control in place of maximum power point tracking to small scale, low voltage photovoltaic (PV) distributed generators. The study is performed in the context of rooftop mounted PV, where the distributed generators contribute primarily to residential loads. The study begins by investigating the design of a single phase 240 VRMS inverter. The design of the inverter uses traditional methods such that either maximum power point tracking or droop control could be applied as the control method for the inverter. The investigation continues by reviewing the principles of droop control and developing the droop control method that is most representative of the low voltage system, referred to in this paper as resistive droop control. The control method is then applied to the inverter design and a microgrid of distributed generator inverters and loads is simulated. The performance of the decentralized control method is analyzed. Potential benefits and applications of this method in the control of microgrids are presented.
Keywords: Renewable energy; Microgrid; Droop control; Inverter; Single phase; Distributed generator